STRATEGI BELAJAR BERBASIS ANEKA SUMBER - Rosa Meriyana A (Perspektif Ilmu Pendidikan, 2006)
The advancement of information and communication technoloy has significant impacts into all aspects of human life including in education. The teachers and the text books are not the only learning resources for the student any more. As there are abundant informations available for students to meet their learning needs. The informations are presented in various media and easy to access. Teaching and learning process at the education institutions should be adjusted to the availability of learning resources. This article discussess Resource Based Learning (RBL) by clarifying the concept, describing how to implement of RBL and showing the example of RBL implementation in Indonesia. It concludes that RBL can solve a number of learning problems particularly in long life education. Therefore, as early as possible everybody should learn how to learn by using RBS.